Konsep Pendidikan Anti Korupsi dalam Al-Quran - Idah, Dede; Aziz, Abdul (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2016)
Quran is the fundamental basis for Islamic education, including the concept of anti-corruption education. With hewn concept of anti-corruption education of the Quran, then the anti-corruption education practices perpetrated by Muslim educators will have a spiritual charge. The Muslim educators feel that the anti-corruption education accomplishments not only as a national educational demands, but also as a command of Allah. With two of these incentives, then the Muslims will be more committed as educators to conduct anti-corruption. This is important in view of the acts of corruption, especially in the educational environment. By using descriptive method, this study concluded that the anti-corruption education according to the Quran includes education to form four following manners: a) honest; b) discipline; c) responsibility; and d) hard work, which are based on the faith education. tors , contents, methods, teaching media, space and time, and showed a close relevance to the development of education today, education in general and education in particular with the Islamic style.